Protective effect of platelet-rich plasma on LPS-induced neuroinflammation in BV2 microglia through NRF2/HO-1 pathway - Yinghui WANG; Ya ZHANG; Zilin WANG; Zixin ZHU; Qiuju MOU; Lili ZHU (Zhongguo shuxue zazhi, 2023)
Objective To investigate the protective effect and mechanism of platelet-rich plasma (PRP) on lipopolysaccharide (LPS) -induced inflammatory response in BV2 cells. Methods BV2 microglia were divided into normal control group, 10%PRP control group, LPS group (LPS induction), 3%PRP+ LPS group (LPS induction, 3%PRP pretreatment), 5%PRP+ LPS group (LPS induction, 5%PRP pretreatment), 10%PRP+ LPS group (LPS induction, 10%PRP pretreatment), and the proliferation of BV2 cells was measured by CCK-8. The mitochondrial membrane potential of BV2 cells was measured by confocal microscopy, ROS was measured by fluorescence method, and NO was measured by Griess method. The protein expressions of IL-6, TNF-α, BACH1, GPX4, NRF2 and HO-1 were detected by Western blot. In addition, BV2 microglia were treated with HO-1 inhibitor and divided into normal control group, LPS group, ZnPP+ LPS group, 10%PRP+ LPS group, ZnPP+ LPS+ 10%PRP group, and the protein expressions of HO-1, IL-6 and TNF-α were detected by Western blot. Results Compared with normal control group, PRP promoted the proliferation of BV2 cells (P<0.01). The mitochondrial membrane potential decreased, ROS production increased, the levels of NO, IL-6, TNF-α and BACH1 increased (P<0.01). However, the expression levels of GPX4, NRF2 and HO-1 decreased (P<0.01) in LPS group. Compared with LPS group, the proliferation activity and mitochondrial membrane potential of BV2 cells in 3%PRP+ LPS, 5%PRP+ LPS and 10%PRP+ LPS groups significantly increased. The levels of ROS, NO, IL-6, TNF-α and BACH1 significantly decreased (P<0.01). The expressions of GPX4, NRF2 and HO-1 in different concentrations of PRP (3%, 5% and 10%) increased (P<0.01). Moreover, the expression of IL-6 and TNF-α in ZnPP+ LPS group was significantly higher than that in LPS group after HO-1 inhibitor treatment. Compared with 10%PRP+ LPS+ ZnPP group, HO-1 inhibitor could reverse the effect of PRP on the expression of IL-6 and TNF-α in LPS-induced BV2 cells (P<0.01). Conclusion PRP inhibits the inflammatory response of BV2 microglia induced by LPS by activating the NRF2/HO-1 signaling pathway.